Predictive value of lung ultrasound score in weaning from mechanical ventilation in neonatal respiratory distress syndrome - Mengwen Li; Maojun Li; Jie Feng; Feng Xiao; Qian Yang (Italian Journal of Pediatrics)
Abstract Background To explore the predictive value of lung ultrasound score (LUS) in weaning from mechanical ventilation in neonatal respiratory distress syndrome (RDS). Methods A total of 111 neonates with RDS who received mechanical ventilation in the neonatal intensive care unit (NICU) of Sichuan Provincial People’s Hospital were selected as the subjects. Before weaning, the LUS was performed by the 12-region ultrasound score of the lungs. Those neonates were divided into the weaning success group (n = 95) and weaning failure group (n = 16) according to whether they received mechanical ventilation again 48 h after weaning. Oxygenation index (OI) before weaning and arterial blood gas indexes after weaning were collected. The correlation of LUS with OI or arterial blood gas was analyzed, and the difference in LUS between the two groups was compared. The receiver operating characteristic (ROC) curve of LUS in predicting the weaning outcome of mechanical ventilation in neonatal RDS was drawn and its predictive value was verified. Results LUS of all neonates before weaning was significantly correlated with OI and arterial blood gas indexes, which was positively correlated with OI value (r = 0.671, p < 0.001) and arterial partial pressure of carbon dioxide (r = 0.461, p < 0.001), and negatively correlated with arterial partial pressure of oxygen (r = -0.531, p < 0.001). The LUS in the weaning success group was significantly lower than that in the weaning failure group (5(3,8) points vs. 12.5(10,16.75) points, p < 0.001). The ROC curve showed that the AUC was 0.898. The optimal cut-off value of LUS was 9.5 as the predictive value of successful weaning, with a sensitivity of 0.875 and a specificity of 0.811. Conclusion LUS is a convenient, sensitive, and accurate predictor of successful weaning of mechanical ventilation in NRDS, and can be used as an important tool for clinical guidance of weaning.